Determinan perempuan bekerja di Jawa Barat - Karina Damayanti (Research Centre for Population, National Research and Innovation Agency (BRIN), 2021)
This study aims to determine the characteristics of female labor force, women’s main employment, and the individual and contextual factors that influence those two situations in West Java Province. The data sources used for this study are National Social-Economic Survey on March 2018 as well as publications on Gross Domestic Product (GDP) and Statistics of Education. This study applies three-levels binary logistics (individual, household, and city/regency) for data analysis. The independent variables that significantly affects women’s employment status are age, education, marital status, household per capita expenditure, number of non-productive household members, household members, sex ratio, residence status, GDP per capita, agricultural contribution to GDP, and mean years schooling. However, access to information does not significantly influence the working status of women. This paper indicates that education is the primary determinant factor in regard to women’s participation in labor force. Education is suggested to improve women’s skills and knowledge that resulted in the advancement of the quality of female labors.